ETHNOMATHEMATICS IN MEASURING RICE FIELD AREAS IN ONE OF THE AREAS IN INDRAMAYU - Eyus Sudihartinih (IAIN Ambon, 2020)
Ethnomathematics is important in learning mathematics. Ethnomathematics is a mathematical education that integrates cultural values in mathematics learning needs to initiate a real integration of cultural values. West Java Society is one of the provinces in Indonesia which has a variety of ethnomathematics, one of which is Indramayu. The Indramayu community generally has a livelihood as a farmer so that most of the Indramayu region is agricultural land, even rice fields can be found even though it is located in the center of Indramayu city. In this article, ethnomathematics is examined in the culture of measuring rice field area in Indramayu. This research method is ethnographic with two participants, a 59-years-old man and a 51-year-old woman from Indramayu. The results of this study are the existence of rice field formulas used by the Truwali Indramayu community.